A Study On Students Interest And Preparedness Based On Entry Survey - Ahmad, Arfah; Anwar Apandi, Nur Ilyana; Hashim, Mohd. Ruzaini; Md Sani, Zamani (2012)
Abstract— The Faculty of Electrical Engineering, UTeM produces students in Bachelor Degree of Electrical Engineering and Mechatronics Engineering. The curriculum of the program was developed based on the Programes Outcomes (PO) set by the faculty committee. Entry survey is a form of survey that was conducted to students that just after their admission into the faculty. The purpose of this survey is to find out the student’s interest and preparedness to learn electrical and mechatronics engineering educations. All of the items in the survey were developed based on POs set by the faculty. A sample of 131 students participated in this survey and the results were analyzed using mean score analysis. Result from the study shows that students admitted to this faculty were prepared enough to study engineering education, hence faculty POs set would be able to roduce a competent engineers.